An increase in neutrophil-to-lymphocyte ratio predicts poor functional outcomes in older patients with acute ischemic stroke: a retrospective study - Jie Xue; Xiao-Guang Zhang; Hua-Yu Jiang; Xian-Kai Cui; Dong Zhang; Zhi-Wen Yao; Yun-Hua Yue (Journal of Integrative Neuroscience, 2021)
The neutrophil-to-lymphocyte ratio has emerged as a predictor of functional outcome in stroke patients. However, less is known about the value of neutrophil to lymphocyte ratio in older patients. This clinical study evaluated whether the neutrophil-to-lymphocyte ratio is associated with stroke severity and early clinical outcomes in older patients with acute ischemic stroke. This observational study included acute ischemic stroke patients aged 80 years or older. The patients were divided into three groups, and information was collected, including demographic, clinical and laboratory data. The neutrophil associations to lymphocyte ratio with stroke severity and early clinical outcomes were assessed with logistic regression. Overall, 356 older patients were enrolled in this study, with a median age of 85.0 (82.0–88.0). Split by tertiles of neutrophil-to-lymphocyte ratio, 118 patients were in the bottom tertile (<2.17), 118 patients were in the middle tertile (2.17–3.36), and 120 patients were in the top tertile (>3.36). After multivariable analysis, patients in the highest tertile were likely to have moderate to severe stroke on admission (OR 4.87, 95% CI, 1.93–12.30, P = 0.001), higher risks of primary unfavorable outcome (OR 2.70, 95% CI, 1.09–6.69, P = 0.032) and secondary unfavorable outcome (OR 2.00, 95% CI, 1.00–4.00, P = 0.050) compared to the lowest tertile. Our finding demonstrated that the neutrophil-to-lymphocyte ratio is an independent predictor of stroke severity and early clinical outcomes in older patients with acute ischemic stroke.